Penerapan Model Pembelajaran Self Directed Learning Pada Materi Dampak Sosial Informatika Terhadap Hasil Belajar Siswa Kelas VII di SMP Negeri 5 Samarinda: Penelitian - Muhammad Zidan; Dewi Rosita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study was conducted in response to low student learning outcomes on the topic of the Social Impact of Informatics, which was attributed to the dominance of lecture-based teaching methods that limited student independence and engagement. The research aimed to evaluate the effectiveness of the Self-Directed Learning (SDL) model in enhancing the learning outcomes of seventh-grade students at SMP Negeri 5 Samarinda. Using a pre-experimental one-group pretest-posttest design, the study involved 24 students. Data were collected through pretest and posttest assessments, observation sheets, and student response questionnaires. The results showed a notable improvement in learning outcomes, with the average pretest score of 70 increasing to 89.17 in the posttest. N-Gain analysis produced a score of 0.63, indicating a moderately effective learning gain. In addition, student responses to the SDL model were highly positive, with an average questionnaire score of 81.29%, demonstrating strong acceptance and enthusiasm for independent learning approaches.